National policy for restructuring the Vietnamese rice sector: Towards 2020 and Vision to 2030 - CGIAR Research Program on Rice (2021)
The new strategy was approved by the Minister of Agriculture and rural development in Decision 1889/QĐ-BNN-TT dated 23 May 2016 by MARD Minister.